Legal Renewal on Addressing Risky Road User Behavior to Reduce Traffic Accident Fatalities Based on a Traffic Criminology Approach in Indonesia - Diamond Romansa Bangun; Supardi Hamid; Kif Aminanto (Indonesian Journal Publisher, 2026)
This study aims to analyze the weaknesses of the traffic law system in handling risky behavior of road users, examine risky behavior as a form of modern crime from a traffic criminology perspective, and formulate legal reconstruction and reform to reduce traffic accident fatalities in Indonesia. The study employs a normative juridical method with a statutory and conceptual approach through an analysis of Law Number 22 of 2009 concerning Traffic and Road Transportation, Law Number 2 of 2002 concerning the Indonesian National Police, as well as various criminological theories and behavioral regulation concepts. The results of the study indicate that the high fatality rate of traffic accidents is predominantly caused by risky behavior of road users, such as speeding, reckless driving, use of mobile phones while driving, illegal racing, underage drivers, and aggressive driving behavior, which is reinforced by the influence of social media and the development of digital technology. The traffic law system in Indonesia is still repressive and administrative in nature, so it has not been able to control dangerous behavior in a preventive and predictive manner. Therefore, legal reform is needed through strengthening the traffic criminology approach, reformulating legal norms based on risk levels, integrating digital surveillance and artificial intelligence, strengthening predictive policing, developing behavioral traffic regulations, and fostering a traffic safety culture based on protecting the right to life and public safety. These legal reforms are expected to create a more adaptive, effective road safety system oriented toward preventing traffic accident fatalities in Indonesia.